COVID-19, COPD, and AECOPD: Immunological, Epidemiological, and Clinical Aspects - Polverino, Francesca; Kheradmand, Farrah (Frontiers in Medicine, 2021)
The newly identified severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) causes several heterogeneous clinical conditions collectively known as Coronavirus disease-19 (COVID-19). Older patients with significant cardiovascular conditions and chronic obstructive pulmonary disease (COPD) are predisposed to a more severe disease complicated with acute respiratory distress syndrome (ARDS), which is associated with high morbidity and mortality. COPD is associated with increased susceptibility to respiratory infections, and viruses are among the top causes of acute exacerbations of COPD (AECOPD). Thus, COVID-19 could represent the ultimate cause of AECOPD. This review will examine the pathobiological processes underlying SARS-CoV-2 infection, including the effects of cigarette smoke and COPD on the immune system and vascular endothelium, and the known effects of cigarette smoke on the onset and progression of COVID-19. We will also review the epidemiological data on COVID-19 prevalence and outcome in patients with COPD and analyze the pathobiological and clinical features of SARS-CoV-2 infection in the context of other known viral causes of AECOPD. Overall, SARS-CoV-2 shares common pathobiological and clinical features with other viral agents responsible for increased morbidity, thus representing a novel cause of AECOPD with the potential for a more long-term adverse impact. Longitudinal studies aimed at COPD patients surviving COVID-19 are needed to identify therapeutic targets for SARS-CoV2 and prevent the disease’s burden in this vulnerable population.